Predicting recycling behavior by including moral norms into the theory of planned behavior - Poškus, Mykolas Simas (Psichologija, 2015)
The theory of planned behavior is a popular and well grounded model of predicting and explaining behavior; however, some researchers propose that in the case of sustainable behavior the model could benefit from the inclusion of moral norms as an additional variable. A paper-and-pencil survey has been carried out to test the assumption that the addition of moral norms can improve the theory of planned behavior in the case of recycling behavior. A sample of 142 university students participated in the study, their mean age was 20 years (SD = 2.5). Participants filled in questionnaires that measured constructs of the theory of planned behavior and moral norms regarding recycling. The results have shown that in the case of recycling behavior, the addition of moral norms to the theory of planned behavior increases the amount of explained behavioral variance. These findings suggest that when using the theory of planned behavior for recycling and perhaps sustainable behavior in general, researchers should consider adding moral norms as an additional predictor of behavioral intention and perhaps behavior as well.